Hydroquinone; A Novel Bioactive Compound from Plant-Derived Smoke Can Cue Seed Germination of Lettuce - Kamran, Muhammad; Khan, Abdul L.; Ali, Liaqat; Hussain, Javid; Waqas, Muhammad; Al-Harrasi, Ahmed; Imran, Qari M.; Kim, Yoon-Ha; Kang, Sang-Mo; Yun, Byung-Wook; Lee, In-Jung (Frontiers in Chemistry, 2017)
Plant–derived smoke has been known to play an important role in distribution and growth of vegetation. Using a proficiently designed furnace, we extracted smoke from the leaves of four plant viz. Helianthus annuus, Aloe vera, Ginkgo biloba, and Cymbopogon jwarancusa. Smoke dilutions obtained from these plants were obtained in different concentrations to identify potential lettuce growth promoting smoke solution. Results revealed that smoke obtained from Ginkgo biloba significantly enhanced the lettuce seed germination. This solution was then partitioned into ethyl acetate, dichloromethane, n-hexane, chloroform and ether fractions. Ethyl acetate fraction was found to be potent to enhance seed germination. This fraction was subjected to column chromatography and spectroscopic techniques to obtain compound 1. This compound was identified as hydroquinone using 1D and 2D NMR techniques. At low concentrations (5, 10 and 20 ppm), compound 1 enhanced the lettuce seed germination; however, higher concentrations inhibited its growth as compared to control.